Interactions Between Gut Microbiota, Host, and Herbal Medicines: A Review of New Insights Into the Pathogenesis and Treatment of Type 2 Diabetes - Zheng, Yujiao; Gou, Xiaowen; Zhang, Lili; Gao, Hanjia; Wei, Yu; Yu, Xiaotong; Pang, Bing; Tian, Jiaxing; Tong, Xiaolin; Li, Min (Frontiers in Cellular and Infection Microbiology, 2020)
Herbal medicines (HMs) are a major subset of complementary and alternative medicine. They have been employed for the efficient clinical management of type 2 diabetes mellitus (T2DM) for centuries. However, the related underlying mechanisms still remain to be elucidated. It has been found out that microbiota is implicated in the pathogenesis and treatment of T2DM. An interplay between gut microbiota and host occurs mainly at the gastrointestinal mucosal barrier. The host movements influence the composition and abundance of gut microbiota, whereas gut microbiota in turn modulate the metabolic and immunological activities of the host. Intestinal dysbiosis, endotoxin-induced metabolic inflammation, immune response disorder, bacterial components and metabolites, and decreased production of short-chain fatty acids are considered significant pathogenic mechanisms underlying T2DM. The interaction between gut microbiota and HMs during T2DM treatment has been investigated in human, animal, and in vitro studies. HMs regulate the composition of beneficial and harmful bacteria and decrease the inflammation caused by gut microbiota. Furthermore, the metabolism of gut microbiota modulates HM biotransformation. In this review, we have summarized such research findings, with the aim to improve our understanding of the pathogenesis and potential therapeutic mechanisms of HMs in T2DM and to provide new insights into specific targeted HM-based therapies and drug discovery.